Starting over : feminism and the politics of cultural critique - Newton, Judith Lowder (Critical perspectives on women and gender., 1994)
For more than a decade Judith Newton has been at the forefront of defining and promoting materialist feminist criticism. Starting Over brings together a selection of her essays that chart the establishment of feminist literary criticism in the academy and its relation to other forms of cultural criticism, including Marxist, post-Marxist, new historicist, and cultural materialist approaches, as well as cultural studies.